Pengaruh Online Customer Review, Online Customer Rating, Live Streaming, dan Brand Reputation Terhadap Keputusan Pembelian Produk Brand 3second di Marketplace Shopee - Andari Sonaria; Any Urwatul Wusko (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the influence of Online Customer Reviews, Online Customer Ratings, Live Streaming, and Brand Reputation on purchasing decisions for 3Second brand products on the Shopee marketplace. This study uses the Stimulus-Organism-Response (S-O-R) theory and a quantitative approach with a survey method and purposive sampling technique. The sample size consists of 125 respondents who are Shopee users who have purchased 3Second products. Data was collected through an online questionnaire using a 5-point Likert scale and processed using SPSS version 25. Instrument validation and reliability tests were conducted. Classical assumption tests included normality, linearity, multicollinearity, and heteroscedasticity tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results of the study indicate that, partially, only the Live Streaming and Brand Reputation variables have a significant effect on purchasing decisions, while Online Customer Reviews and Online Customer Ratings do not have a significant effect. Simultaneously, all four variables significantly influence purchasing decisions with an R² value of 0.639. This means that 63.9% of the variability in purchasing decisions can be explained by these four independent variables, with Brand Reputation being the most dominant variable in influencing consumer purchasing decisions compared to other variables, while the rest is influenced by factors outside the model.